Arrive as guests and leave as friends : the role of hedonic experiences in the luxury context - Veloso, Daniela Moita (2023)
This research was conducted to understand the role of personalized customer service in the customers’ hedonic experiences. A main objective was imposed in the research to fathom the relationship between the two factors, being made research the spectrum of luxury hospitality from the perspective of managers and customers. The purpose of the study falls under the principle that customer service is the key to a successful business. Twenty interviews were conducted with people on both sides of the coin – employees and guests – answering open-ended questions regarding the topic. In conclusion, it was found that personalized customer service undoubtedly impacts the guest's hedonic experience. Moreover, employees who are at the center of this effect play a major role in the overall hedonic experience.